Two-warehouse inventory model for non-instantaneous deteriorating items with stock dependent demand, partial backlogging and inflation over a finite time horizon. (2016) - Palanivel, M.; Uthayakumar, R.
In this paper, two-warehouse economic order quantity (EOQ) model for non-instantaneous deteriorating items with stock dependent demand under the effect of inflation and time value of money over a finite planning horizon is presented. Also in this model, shortages are allowed and partially backlogged. The backlogging rate is dependent on the waiting time for the next replenishment. This paper aids the retailer in minimising the total inventory cost by finding the optimal interval and the optimal order quantity. An algorithm is designed to find the optimum solution of the proposed model. Numerical examples are given to demonstrate the results. Also, the effect of changes in the different parameters on the optimal total cost is graphically presented and the implications are discussed in detail.